IDENTIFICATION OF RICE GENOTYPES RESPONSIBLE FOR HIGH-EFFICIENT AND LOW-EFFICIENT MICRONUTRIENTS CONTENTS - Shafiq ur Rahman Memon; Saima Parveen Memon; Maaz Ullah; Amna Arif; Mahnoor Aslam; Manahel Azhar; Huagang Huang; Zicheng Zheng; Ayesha Noor (International Journal of Contemporary Issues in Social Sciences, 2024)
Micronutrient raises to the relative quantity of a nutrient that is prerequisite for plant growth. It takes part in metabolic activities, enzymatic process/catalysts and these all directly and in-directly support in plant growth development and essential to alive organisms for normal growth and reproduction. The incidence of micronutrient deficiency has increased in recent year. An experiment was undertaken to investigate the important micronutrients under laboratory conditions in the Plant Nutrition, College of Resources, Sichuan Agricultural University, Chengdu, Sichuan Provine of China. A total of seventy (70) different commercial rice genotypes were tested to assess Zinc (Zn), Iron (Fe), Copper (Cu) Manganese (Mn) and Selenium (Se) contents in rice grain. These contents were determined by using Optical Emission Spectrometry (OES) with Acid Digestion method. The samples were digested by using the application of acid mixture which includes nitric acid (HNO3): and perchloric acid (HClO4). Results revealed that four Mn and Cu, three Fe, eight Zn and two Se rice genotypes were high contents in rice grain. However, the lowest grain contents were recorded in two genotypes in Mn, three genotypes in Fe, Cu and Zn and two genotypes in Se. The highest Zn content 37.73 mg kg-1 was documented in ZJ-14 genotype and lowest 18.28 mg kg-1 in ZJ-29. The highest Fe 23.73 mg kg-1 content was found in YR-5 genotype and lowest 8.68 mg kg-1 in ZJ-25. However, the highest Cu content 4.99 mg kg-1 was found in ZJ-11 genotype and lowest 1.34 mg kg-1 in ZJ-26. In case of the highest Mn content 54.16 mg kg-1 was recorded in ZJ-17 mg kg-1 genotype and lowest 17.94 mg kg-1 in ZJ-28. The ZJ-22 genotype was revealed the highest Se content 0.56 mg kg-1 and YR-30 was found in lowest contents 0.04 mg kg-1 of Se. Hence, from the results it shows the variation among the selected commercial rice genotypes for micronutrients status in grains and indicated the different behavior of the genotypes for the uptake of micronutrients.